Analytical support of management activities in the context of management accounting standardization - K. Berkaeva, Albina (2020)
The development and improvement of national accounting and management accounting is accompanied by the introduction of new methods for analysis and diagnosing the final result. So, the point approach in the management of assets and liabilities involves a quantitative and qualitative characteristic of the resulting economic situations (consequences) in production and financial activities. This does not happen spontaneously, but as the business management system develops.Recently, there has been the increase of interest in the analysis of profitability in relation to different segments of sales, diagnostics of margin indicators, etc.